INTERPRETATION OF PRAGMATIC MEANS OF NARRATION IN THE NOVEL “JANE EYRE” - Nasreddinova Farzona Shuxratovna (Modern American Journals, 2025)
This article examines how Charlotte Brontë uses language in “Jane Eyre” to do more than just tell a story. It focuses on pragmatic tools such as speech acts, indirect meaning (implicature), politeness, and deixis to show how the main character, Jane, expresses her identity and deals with social power. The analysis is based on ideas from well-known scholars like Grice, Searle, Brown and Levinson, and Bakhtin. By looking closely at important parts of the novel, the article shows that Jane’s way of speaking changes as she grows stronger and more independent. These language choices also help Brontë involve the reader and highlight deeper themes like gender and personal freedom. The study concludes that pragmatic analysis helps us better understand how characters communicate and how novels create meaning through language.
Keywords: pragmatic means, speech acts, implicature, politeness theory, deixis, narrative voice, identity, power, reader engagement